Performance analysis of the IEEE 802.16J WiMAX relay network / Ariffin Narwes Muhammad Juhin - Muhammad Juhin, Ariffin Narwes (2015)
WiMAX MMR (Worldwide interoperability for micro wave access technology) is a new technology in enabling access of wireless network widespread. The IEEE 802.16j for Mobile Multi Hop relay (MMR) network was approved in 2009 by the IEEE 802.16 working committee. Other than mobility support, IEEE 802.16j also implements relay stations (RS) to the network which helps packets transfer by connecting the base station (BS) and a mobile station (MS). Once a mobile station is obstructed by building or terrain, the mobile station will experience a low quality channel headed for the base station. Implementation of the relay can improve the condition and enabling it to achieve higher throughput transfer from or to the base station. As the IEEE 802.16j is a new standard, knowledge on the performance of the network has become valuable. Hence, this study focuses on analyzing and evaluating the performance of real time traffic applications. This research will examine the performance of throughput, packet loss, and fading type of the WiMAX standard. It will also be focused on the transparent mode of the relay. The NCTUns 6.0 is used as a tool to simulate the network environment. Results from the simulation show that video conferencing and VoIP delivering performance are in compromise to the performance metrics thus, proving the ability of WiMAX MMR to handle real time traffics in the network environment.